Mental workload during endoscopic sinus surgery is associated with surgeons’ skill levels - Suzuki, Masanobu; Miyaji, Kou; Matoba, Kotaro; Abe, Takashige; Nakamaru, Yuji; Watanabe, Ryosuke; Suzuki, Takayoshi; Nakazono, Akira; Konno, Atsushi; Hinder, Dominik; Psaltis, A. J.; Wormald, P. J.; et al. (Frontiers in Medicine, 2023)
Introduction Surgeons’ mental workload during endoscopic sinus surgery (ESS) has not been fully evaluated. The assessment was challenging due to the great diversity of each patient’s anatomy and the consequence variety of surgical difficulties. In this study, we examined the mental workload of surgeons with various surgical skill levels during ESS under the standardized condition provided by novel-designed 3D sinus models. Materials and methods Forty-seven participants performed a high-fidelity ESS simulation with 3D-printed sinus models. Surgeons’ mental workload was assessed with the national aeronautics and space administration-task load index (NASA-TLX). Associations between the total and subscales score of NASA-TLX and surgical skill index, including the board certification status, the number of experienced ESS cases, and the objective structured assessment of technical skills (OSATS), were analyzed. In addition, 10 registrars repeated the simulation surgery, and their NASA-TLX score was compared before and after the repetitive training. Results The total NASA-TLX score was significantly associated with OSATS score (p = 0.0001). Primary component analysis classified the surgeons’ mental burden into three different categories: (1) the skill-level-dependent factors (temporal demand, effort, and performance), (2) the skill-level-independent factors (mental and physical demand), and (3) frustration. After the repetitive training, the skill-level-dependent factors were alleviated (temporal demand; z = −2.3664, p = 0.0091, effort; z = −2.1704, p = 0.0346, and performance; z = −2.5992, p = 0.0017), the independent factors were increased (mental demand; z = −2.5992, p = 0.0023 and physical demand; z = −2.2509, p = 0.0213), and frustration did not change (p = 0.3625). Conclusion Some of the mental workload during ESS is associated with surgical skill level and alleviated with repetitive training. However, other aspects remain a burden or could worsen even when surgeons have gained surgical experience. Routine assessment of registrars’ mental burdens would be necessary during surgical training to sustain their mental health.